1999
DOI: 10.1080/030919099294311
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of relaxed excised skin exhibiting striae distensae

Abstract: Tensile properties of skin determine some important physical attributes of skin. They may be conveniently assessed using recent technologies. The aim of the study was to compare ex vivo the tensile properties of normal looking skin and striae distensae. The Cutometer was used with 2 and 4 mm diameter probes. Skin distensibility values were dependent on the suction force and area of the skin tested. Conversely, tensile ratios yielding elasticity parameters were not affected by the same variables. Although tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
0
22
1
Order By: Relevance
“…Although the skin is known to be anisotropic for large strains [14], previous shear experiments indicated that for low strains the skin of young adults can be considered isotropic [6, 12]. Our data are at variance with such a contention.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the skin is known to be anisotropic for large strains [14], previous shear experiments indicated that for low strains the skin of young adults can be considered isotropic [6, 12]. Our data are at variance with such a contention.…”
Section: Discussioncontrasting
confidence: 57%
“…In some instances, both the structure and mechanical properties of the dermal fibrous networks are altered 27 . Ruptures supervene in the direction of minimal tensions where the tissue is the weakest to sustain the mechanical stress 3,27,28 . As a result, the long axis of striae distensae is orientated along the skin tension lines, and the damages resulting from the rupture occur in the direction normal to the long axis of the striae 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Force tranductions affect the structure of the dermis 6 and the functions of different cell lineages as well 8–11 . Striae are largely parallel to the relaxed tension lines that show the orientation of minimal skin extensibility 12–14 . They result from a failure of the skin to elongate under low‐intensity forces, with ultimate brittleness of the dermis.…”
Section: Introductionmentioning
confidence: 99%